IgG1 pan-neurofascin antibodies define a severe and frequently fatal GBS-like neuropathy which responds to rituximab. Issue 6 (27th May 2022) - Fehmi, Janev; Jon Walters, R; Lavin, Tim; Keh, Ryan; Rossor, Alexander M; Munteanu, Tudor; Delanty, Norman; Roberts, Rhys; Baumer, Dirk; Rinaldi, Simon
Abstract : Importance: Disease modifying treatments in Guillain-Barré syndrome (GBS) are not tailored to the different pathological subtypes. Strategies to prospectively identify sub-sets of patients with specific disease mecha- nisms and inform the use of non-standard therapies may lead to improved outcomes. We present a case series of seven patients with IgG1 subclass pan-neurofascin antibodies. Results: All seven patients presented with a severe, acute or sub-acute onset, predominantly motor, autoimmune neuropathy. In all but one case the neuropathy was severe enough to warrant mechanical ventilation and intensive care support. Cranial nerve deficits were universally present and autonomic dysfunction was common. Although clinically resembling GBS, the response to standard GBS therapies was poor. Four patients received the B-cell depleting therapy rituximab and showed significant and sustained functional improvement within weeks of treatment. The three remaining patients who did not receive rituximab died. Conclusions and Relevance: These observations should lead to a re-evaluation of the benefit of nodal/paranodal antibody testing in neuropathies with acute onset, GBS-like presentations. We believe that such testing should form part of the routine diagnostic work up of such patients, and that the identifica- tion of a distinct, serologically-defined disease sub-type should prompt consideration of more targeted immunotherapy. The apparent benefit of rituximab reported here should be evaluated in a well-conduc- ted clinical trial, the design of which must consider the potentially grave outcome in pan-neurofascin antibody-positive patients receiving only standard therapies. simon.rinaldi@nhs.net